Insight into the X‐ray absorption spectra of Cu‐porphyrazines from electronic structure theory. Issue 3 (26th October 2020) - Boydas, Esma Birsen; Winter, Bernd; Batchelor, David; Roemelt, Michael
Abstract: Transition metal porphyrazines are a widely used class of compounds with applications in catalysis, organic solar cells, photodynamic therapy, and nonlinear optics. The most prominent members of that family of compounds are metallophtalocyanines, which have been the subject of numerous spectroscopic and theoretical studies. In this work, the electronic structure and X‐ray absorption characteristics of three Cu‐porphyrazine derivatives are investigated by means of modern electronic structure theory. More precisely, the experimentally observed N K‐edge and Cu L‐edge features are presented and reproduced by time‐dependent density functional theory, restricted open‐shell configuration interaction, and a restricted active space approach. Where possible, the calculations are used to interpret the observed spectroscopic features in terms of electronic transitions and, furthermore, to connect spectral differences to chemical variations. Part of the discussion of the computational results concerns the impact of various parameters and approximations that are used for the calculations, for example, the choice of active space. Abstract : Transition metal porphyrazines are a widely used class of compounds with various fields of application. This work reports on the N K‐edge and Cu L‐edge absorption spectra of a series of Cu porphyrazines, together with their simulation and interpretation, by means of state‐of‐the‐art electronic structure methods.